Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

```latex
\begin{array}{c}
x + 6y = 5 \\
3x - 7y = -35 \\
\text{Solution: } (-7, 2)
\end{array}

\begin{aligned}
x + 6y &= 5 \\
-2y &= -50
\end{aligned}

The solution to System B will be the same as the solution to System A.
```


Sagot :

Sure, let's solve the given system B step-by-step:

[tex]\[ \begin{aligned} 1) & \quad x + 6y = 5 \\ 2) & \quad -2y = -50 \end{aligned} \][/tex]

First, isolate [tex]\( y \)[/tex] in the second equation:

[tex]\[ -2y = -50 \][/tex]

Divide both sides by -2:

[tex]\[ y = \frac{-50}{-2} \Rightarrow y = 25 \][/tex]

Now that we have [tex]\( y = 25 \)[/tex], substitute this value into the first equation [tex]\( x + 6y = 5 \)[/tex]:

[tex]\[ x + 6(25) = 5 \][/tex]

Simplify inside the parenthesis:

[tex]\[ x + 150 = 5 \][/tex]

Next, isolate [tex]\( x \)[/tex] by subtracting 150 from both sides of the equation:

[tex]\[ x + 150 - 150 = 5 - 150 \Rightarrow x = -145 \][/tex]

So, the solution to the system B is:

[tex]\[ x = -145 \quad \text{and} \quad y = 25 \][/tex]

Thus, the solution is [tex]\((-145, 25)\)[/tex].